Analysis of the remote laser cutting process induced damage in carbon fibre reinforced polymers. Issue 1 (14th December 2021) - Schmidt, Benjamin; Husert, Markus; Rose, Michael; Zimmermann, Martina; Kästner, Markus
Abstract: In this contribution a modelling approach for the laser cutting process simulation of carbon fibre reinforced polymers is introduced. The cutting process is modelled in a 3D thermal simulation, the material is modelled layer‐wise orthotropically. For the evaporation of matrix and fibre phase transitions are utilised. The laser spot is modelled with its gaussian distribution as a heat input on the upper side.